The social dimension of Shin Buddhism - Dessì, Ugo. (Numen Book Series, 2010)
Shin Buddhism (Jōdo Shinshū), although weakened in many ways by secularization, continues to be a stable presence in Japanese society, as is emblematically shown by the very symmetrical position of the Nishi (Honganji-ha) and the Higashi Honganji (Ōtani-ha) head temples in the center of Kyōto, and by the recent projects for their renovation. This book addresses the need for more academic research on Shin Buddhism, and is specifically directed at describing and analyzing distinctive social aspects of this religious tradition in historical and contemporary perspective. The contributions collected here cover a wide range of issues, including the intersection between Shin Buddhism and fields as diverse as politics, education, social movements, economy, culture and the media, social ethics, gender, and globalization.